A Complete Solution to the Existence of (k, λ)‐Cycle Frames of Type gu. Issue 5 (30th May 2016) - Buratti, M.; Cao, H.; Dai, D.; Traetta, T.
Abstract: The existence problem of a ( k, λ ) ‐cycle frame of type g u is now solved for any quadruple ( k, λ, g, u ) .